Effectiveness of different control measures against western corn rootworm larvae Diabrotica virgifera virgifera LeConte, 1868 - Špela MODIC; Primož ŽIGON; Aleš KOLMANIČ; Tone GODEŠA; Jaka RAZINGER (Acta Agriculturae Slovenica)
The Western Corn Rootworm (WCR), Diabrotica virgifera virgifera LeConte, 1868, [Coleoptera, Chrysomelidae], whose larvae cause damage to maize roots, is an important economic insect pest in America and Europe. Its larvae are usually controlled by granular soil insecticides or insecticide-treated seeds. Biological control options, such as entomopathogenic nematodes (EPN) have played an important role as an alternative for synthetic chemical insecticides. Therefore, for the WCR larvae control we compared the effectiveness of inundative biological control on the basis of EPN Heterorhabditis bacteriophora Poinar, 1976 (Rhabditida: Heterorhabditidae); (commercial product Dianem®) and the conventional insecticides Force 1.5 g (active substance tefluthrin) from the group of synthetic pyrethriods and Sonido (active substance thiacloprid) from the group of neonicotinoids. Field experiments were carried out at geographically different locations under different population pressure of the insect pest in a), Bučečovci (Prlekija; Eastern Slovenia) and b), Šmartno (Gorenjska: northern Slovenia). The differences between the treatments were very similar at both locations; although the population of WCR in Gorenjska was approximately 5-fold lower than in Prlekija. The highest number of WCR beetles was caught in the negative control, followed by the product Sonido, Force and Dianem®, in decreasing order. Statistical analysis showed that only in the treatment where EPN were used, significantly less WCR was caught than in the control. The results of the WCR larvae control in maize using Heterorhabditis bacteriophora are comparable to published literature. However, the weather conditions in the 2016 trial were very favorable for the development and survival of EPN in the soil.